2019
DOI: 10.3390/molecules24112136
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Red Ginseng Saponins in Scopolamine-Treated Rats and Activity Screening Based on Pharmacokinetics

Abstract: Ginseng has been used to alleviate age-related dementia and memory deterioration for thousands of years. This study investigated the protective effect of red ginseng saponins against scopolamine-induced cerebral injury. Meanwhile, pharmacokinetics of ginsenosides in normal and scopolamine-treated rats were compared. After scopolamine injection, glutathione, catalase and superoxide dismutase levels were significantly decreased when compared with control group. Compared with SA group, pretreatment of rats with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…As reported previously, Rg2 showed stronger neuro-protective [ 35 ] and obesity prevention [ 16 ] properties as compared to Re. Therefore, researchers were tempted to convert Re into the minor forms [ 1 , 36 ].…”
Section: Resultssupporting
confidence: 66%
“…As reported previously, Rg2 showed stronger neuro-protective [ 35 ] and obesity prevention [ 16 ] properties as compared to Re. Therefore, researchers were tempted to convert Re into the minor forms [ 1 , 36 ].…”
Section: Resultssupporting
confidence: 66%
“…At present, AChE remains the primary therapeutic target for NDDs. Acetylcholinesterase inhibitors play an important role in the treatment of NDDs (Chen et al., 2019). Studies have reported that cholinesterase could reduce nerve transmission between cholinergic synapses and nerves and muscles, degenerate cholinergic neurons, and lead to the damage of learning‐related neural circuits (Wandhammer et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zheng et al found that the TCM Bu-Shen-Jian-Pi-Fang could inhibit tumor proliferation by enhancing GLUT-1 related glycolysis and may alter the immune-rejection microenvironment in renal cell carcinoma patients ( 37 ). Ginsenoside Re functions as an antioxidant, protecting cardiomyocytes from oxidant injury induced by exogenous and endogenous oxidants, and protects against apoptotic cell death ( 38 , 39 ). Notably, previous attempts to explore the cancer prevention and therapeutic potential of Lut have systematically indicated its potential as an anticancer agent for various cancers ( 40 ).…”
Section: Discussionmentioning
confidence: 99%